2015
DOI: 10.1136/bcr-2015-211761
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally extensive transverse myelitis and meningitis due to a rare infectious cause

Abstract: DESCRIPTIONA previously healthy 9-year-old girl was admitted to the emergency department of a district hospital due to persistent headache for 3 days. Somnolence, fever and meningismus were noticed. No previous infections or recent immunisations were reported. The child had leucocytosis with elevated C reactive protein. Cerebrospinal fluid (CSF) analysis showed pleocytosis of 96 cells, 73% of lymphocytes, with negative bacteriological, enterovirus and herpes simplex virus screen. Ceftriaxone was started. Owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Though rare, infections such as herpes virus (Herpes simplex, 165 Epstein–Barr virus, 166 and cytomegalovirus 167 ), human T-lymphotrophic virus 1 (HTLV-1), 168 dengue virus, 169 Borrelia burgdorferi (Lyme), 170 tuberculosis, 171 Mycoplasma pneumoniae , 172 and Streptococcus pneumoniae 15 can manifest as LETM and/or optic neuritis.…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
See 1 more Smart Citation
“…Though rare, infections such as herpes virus (Herpes simplex, 165 Epstein–Barr virus, 166 and cytomegalovirus 167 ), human T-lymphotrophic virus 1 (HTLV-1), 168 dengue virus, 169 Borrelia burgdorferi (Lyme), 170 tuberculosis, 171 Mycoplasma pneumoniae , 172 and Streptococcus pneumoniae 15 can manifest as LETM and/or optic neuritis.…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
“…Interestingly, though most of the infectious myelitis cases reported absence of AQP4-Ab, 15 , 166 173 several cases have shown that NMOSD with AQP4 can develop several days after zoster infection. 174 176 These findings might imply at least some pathogenic overlap between these two distinctive diseases of NMOSD and herpes zoster.…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection that can cause ON that can mimic NMOSD. [ 24 197 210 252 ] Other infections that can mimic NMOSD include Epstein Barr virus,[ 11 ] herpes simplex virus,[ 190 ] cytomegalovirus,[ 267 ] human t-lymphocytic virus,[ 279 ] dengue fever,[ 147 ] lyme disease,[ 174 ] tuberculosis,[ 100 ] Mycoplasma pneumoniae ,[ 80 ] and Streptococcus pneumoniae . [ 238 ]…”
Section: Clinical Differentiation and Comorbidities Of Neuromyelitis mentioning
confidence: 99%
“…HSV-2 produces Elsberg's syndrome [37], EBV can rarely cause TM and is associated with a poor prognosis [38]. Dengue viral infection could cause an ATM episode as a manifestation, despite only four cases having been reported in the literature [39].…”
Section: Tm and Infectious Diseases Causal Agentsmentioning
confidence: 99%